2017
DOI: 10.1111/spc3.12328
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the biopsychosocial model of health: Understanding health as a dynamic system

Abstract: The biopsychosocial model has dominated research and theory in health psychology. This article expands the biopsychosocial model by applying systems theories proposed by developmental scholars, including Bronfenbrenner's ecological models and Sameroff's transactional model, as well as contemporary philosophical work on dynamic systems. The proposed dynamic biopsychosocial model construes human health as a product of the reciprocal influences of biological, psychological, interpersonal, and macrosystem contextu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
204
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 245 publications
(215 citation statements)
references
References 86 publications
2
204
1
8
Order By: Relevance
“…Despite the fact that in this study we identified certain biological, psychological, interpersonal and contextual factors that are shown to influence the employment of our study group, it is also important to bear in mind the interconnectedness and mutual influence of these factors as presented by Lehman et al [25]. All the biological, psychological and interpersonal challenges that persons with psychiatric disabilities experience are interrelated and also influenced by contextual factors that operate in their environment.…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…Despite the fact that in this study we identified certain biological, psychological, interpersonal and contextual factors that are shown to influence the employment of our study group, it is also important to bear in mind the interconnectedness and mutual influence of these factors as presented by Lehman et al [25]. All the biological, psychological and interpersonal challenges that persons with psychiatric disabilities experience are interrelated and also influenced by contextual factors that operate in their environment.…”
Section: Resultsmentioning
confidence: 78%
“…Identified barriers and facilitators will be discussed separately in accordance with the dynamic representation of bio-psycho-social model by Lehman et al [25]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations